Pyrimidine-5-carbonitriles II: Synthesis and Antimicrobial Activity of Novel 6-Alkyl-2,4-disubstituted pyrimidine-5-carbonitriles - Al-Abdullah, E. S.; Al-Turkistani, A. A.; Al-Deeb, O. A.; El-Brollosy, N. R.; Habib, E. E.; El-Emam, A. A. (Drug Research, 2014)
New series of 6-alkyl-2,4-disubstituted pyrimidine-5-carbonitriles namely, 6-alkyl-2-thiouracil-5-carbonitriles 4c,d, 6-alkyl-2-arylmethylsulfanyl-3,4-dihydro-4-oxopyrimidine-5-carbonitriles 5a–p, 6-alkyl-2-(2-methoxyethylsulfanyl)-3,4-dihydro-4-oxopyrimidine-5-carbonitriles 6a–d, 6-alkyl-2-benzyloxymethylsulfanyl-3,4-dihydro-4-oxopyrimidine-5-carbonitriles 7a–c, 6-alkyl-2-(5-nitrofuran-2-ylmethylsulfanyl)-3,4-dihydro-4-oxopyrimidine-5-carbonitriles 8a–d, 6-alkyl-4-arylthio-2-(benzylsulfanyl)pyrimidine-5-carbonitriles 10a, b and 2-benzylsulfanyl-4-[4-(2-methoxyphenyl)-1-piperazinyl]-6-pentylpyrimidine-5-carbonitrile 11, were synthesized and tested for in vitro activities against a panel of Gram-positive and Gram-negative bacteria and the yeast-like pathogenic fungus Candida albicans. Compounds 4d, 5b, 5c, 5d, 5e, 5f, 5g, 5h, 5i, 5j, 5k, 5 l, 5p, 7a, 7b, 7c, 8a, 8b, 8c, 8d and 11 displayed marked antibacterial activity particularly against the tested Gram-positive bacteria. Meanwhile, none of these compounds were proved to be active against Candida albicans.
Keywords: synthesis; pyrimidines; dihydro-4-oxopyrimidines; antimicrobial activity